Ocean literacy in Brazilian formal education: A tool for participative coastal management - Carmen Edith Pazoto; Michelle Rezende Duarte; Edson Pereira Silva (Australian Journal of Environmental Education)
Ocean literacy (OL) proposes to include ocean and marine environment-related content in school curricula. Such a topic has been deemed effective for citizens to develop actions and attitudes towards the health of marine ecosystems. This study aimed to verify the presence and frequency of OL principles and concepts in the Brazilian high school curriculum at the federal (National Curricular Parameters-PCN) and regional (Rio de Janeiro - Curricular Reference-RC) levels. Both PCN and RC contained OL-related content. Moreover, Biology and Geography were the subjects with the highest numbers of OL concepts, both in the PCN (26 and 27, respectively) and in the RC-RJ documents (28 and 24, respectively), while OL concepts were very little represented in History subject. A Mann–Whitney U-test did not indicate statistically significant differences in the number of concepts between PCN and RC-RJ (p = 0.54). A principal component analysis discriminated the documents according to subjects, regardless of their origin (federal or regional). These results provide an unbiased assessment of the relationship between the curriculum and OL in a strongly affected area (Rio de Janeiro State coastal zone [CZ]). Therefore, these results provide valuable support for managers seeking to promote effective CZ management practices and public compliance.